Case Report: Pheochromocytoma in a 59-Year-Old Woman Presenting With Hypotension - Wu, Hao-Yu; Gao, Tian-Jiao; Cao, Yi-Wei; Liang, Lei (Frontiers in Cardiovascular Medicine, 2021)
Background: Pheochromocytoma patients who present with shock are extremely rare. Here, we report a patient who presented with shock and was diagnosed with pheochromocytoma. Case Summary: A 59-year-old woman with a history of hypertension without any treatment for 5 years presented with chest tightness. Vital signs on arrival indicated blood pressure of 78/50 mmHg. Twelve-lead electrocardiogram indicated ST-segment depression in leads II, III, aVF, and V3–V6 and QT prolongation. Coronary angiogram revealed no evidence of coronary artery disease. Contrast-enhanced computed tomography demonstrated an inhomogeneous right adrenal mass (2.5 × 3.0 cm). Her 24-h urinary norepinephrine and catecholamine levels were elevated. The patient underwent laparoscopic right adrenalectomy. Histopathology confirmed adrenal pheochromocytoma with residual necrosis. The patient was diagnosed with pheochromocytoma. During the 2-year follow-up, the patient was asymptomatic, and her blood pressure remained normal without medication. ECG showed that the ST-segment depression in leads II, III, aVF, and V3–V6 and the QT prolongation had disappeared. The patient showed no signs of recurrence, with normal urine norepinephrine and catecholamine levels. Conclusion: Patients with pheochromocytoma can present with hypotension or even shock. Clinicians should suspect pheochromocytoma when a patient with a history of hypertension has sudden hypotension or even shock.